Regulatory T cells in dogs with multicentric lymphoma: peripheral blood quantification at diagnosis and after initial stage chemotherapy - Munhoz, T. D.; Anai, L. A. [UNESP]; Fonseca, D. M.; Semolin, L. M. [UNESP]; Sueiro, F. R.; Tinucci-Costa, M. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2016)
Lymphoma is the most common hematopoietic malignancy in dogs and one of the most frequent among all neoplastic diseases in this species. It can occur in several anatomical locations with distinct histological and immunophenotypes. Depending on the host immune response towards the tumor, prognosis information could be collected. Because its well established immunosuppressant, antitumor activity, the function of regulatory T cells (Tregs) in canine neoplasias has been investigated. In this study, we sought to quantify, using flow cytometry, the Tregs subpopulation in peripheral blood of healthy dogs (10) and in those diagnosed with type-B (14) and type-T (8) multicentric lymphoma before (at diagnosis) and after the first cycle (5-week) of 19-week Madison-Wisconsin (MW) protocol of chemotherapy. Our results indicated that dogs with lymphoma showed higher percentage of Tregs (18,84+/-2,56) when compared to healthy dogs (4,70+/-0,50) (P<0,01). In addition, 5-week chemotherapy treatment reduced the Tregs subpopulation (7,54+/-1,08) to levels similar to control (4,70+/-0,50) (P>0,05). There was no difference in Tregs percentage between B-type (17,45+/-2,77) and T-type (21,27+/-5,27) lymphoma (P> 0,05). With this, we conclude that canine lymphoma increases Tregs in the peripheral blood and the MW protocol of chemotherapy reduces this cell subpopulation to control values.
Keywords: dogs; multicentric lymphoma; flow cytometry; regulatory T cells